German meteorological activities in the Arctic, 1940–45 - Blyth, J. D. M. (Polar Record, 1951)
Between 1940 and 1945 the German navy undertook a series of expeditions to the arctic regions in order to obtain regular synoptic weather reports, the international exchange of which had practically ceased upon the outbreak of war in 1939. During these years the German naval meteorological service [Wetterdienst des Oberkommandos der Kriegsmarine] organized and dispatched some thirteen parties, whose task it was to provide the information required to meet the exigencies of modern naval warfare and to enable forecasts of the influence of the “polar front” on European weather to be made. Owing to the strategic situation these activities were confined to Svalbard, East Greenland and Zemlya Frantsa-Iosifa (Franz Josef Land). The German air force sent one expedition to Spitsbergen and two to Hopen (Hope Island) but on the whole the Luftwaffe preferred to employ aircraft flying from bases in northern Norway to obtain operational data, making special flights as and when required.